Analysis Impact Application of Average Effective Rate in Calculation of Income Tax Article 21 (Case Study of PT X) - Maharani Pelawi, Novia Dwi; Ayu Wijayanti, Nanda (International Journal Labs, 2025)
This study aims to analyze the impact of the application of income tax article 21 calculation using the average effective rate based on Government Regulation Number 58 of 2023. The analysis was carried out using the concept of cost and benefit analysis of tax management efforts carried out by the Company in responding to changes in the calculation of Income Tax Article 21. The existence of a newly adapted policy requires adjustments to the calculation mechanism that has been carried out, resulting in costs for the company. The study was conducted to determine the amount of costs and benefits obtained by the Company after implementing the calculation with the average effective rate. The study was conducted on the compliance costs incurred by the company to obtain benefits from tax management efforts, namely increasing compliance. This study was conducted from January to June 2024 with the research method used being a qualitative approach with a case study at PT X. The data collection technique used was document analysis of PT X and interviews. The results of the study showed that the benefits obtained by PT X could not be measured in numbers, but the costs incurred by PT X had increased compliance in carrying out tax obligations. The contribution of this study is as information that tax management carried out by PT X is one way to maximize the benefits obtained by the company.